Strategies to Improve Education Quality through Facilities and Infrastructures Management in Singkawang Vocational School - Kornelius Tony (JETL (Journal of Education, Teaching and Learning), 2019)
The school is a social institution whose existence is part of the nation's social system which aims to produce capable, democratic, responsible, faithful, faithful, physically and spiritually healthy individuals, possessing knowledge and skills, having a steady and independent personality. To achieve these objectives, a strong curriculum is needed, both infrastructure and superstructure. This study aimed to reveal the strategy to improve the quality of education through the management of facilities and infrastructure in Singkawang 1 Vocational High School (SMK) with a focus on 1) Facilities and infrastructure planning at Singkawang State Vocational School, 2) The use of facilities and infrastructure in Singkawang Vocational School 1, 3) Supervision of Facilities and Infrastructure at SMK Negeri 1 Singkawang, 4) Reporting on facilities and infrastructure at SMK Negeri 1 Singkawang, 5) Obstacles faced in facilities and infrastructure at SMK Negeri 1 Singkawang. The research method used is descriptive research with a qualitative approach. Data collected by in-depth interviews, participant observation, documentation and analyzed through data reduction, data presentation, conclusions or verification. Data reliability testing is done by extending the observation period, and triangulation and member checking. The results of the study concluded: 1) planning of facilities and infrastructure programs have been made by the student department to develop facilities in school activities. 2) The use of facilities and infrastructure is carried out in accordance with the learning needs by each teacher and regulated and monitored in an orderly manner, 3) Supervision of facilities and infrastructure has been carried out directly by the school principal, 4) Reporting has been carried out periodically by the student body to the principal school, 5) Constraints faced in facilities and infrastructure are financing both for procurement and maintenance. Based on the results of the study suggested the following things: 1) The principal is expected to optimize the supervision of all activities that have been planned so that the specified goals can be achieved. 2) Need to involve the community in the procurement of financing and maintenance of facilities and infrastructure. 3) Teachers, the administration is expected to be involved in the management of facilities and infrastructure.